BENCHMARKING AND ITS ROLE UNDER THE CONDITIONS OF KNOWLEDHE ECONOMY DEVELOPMENT - Natalia V. PRZHEDETSKAYA (Advanced Engineering Research)
Selection criteria of comparison situations are discussed. The structure of relative case analysis and ways of administrative cases creation are defined. The classification of information the companies get at the market is given. The strategy of information society development is formed for extended use of human potential. Some problems to be solved within common information space are set. The lines of the marketing service activity with a use of benchmarking method are substantiated.